Analysis of risk factors associated with pre-myopia among primary school students in the Mianyang Science City Area - xiaoyin wang; Yi-bin Deng; Li-ge Xiao; Hui-Min Wang; Guo-Zhong Zhao; Lian Ye; Da-Wei Men; Mei Yan (Bern Open Publishing, 2024)
Objectives To find out the prevalence rate of pre-myopia among primary school students in the Mianyang Science City Area, analyze its related risk factors, and thus provide a reference for local authorities to formulate policies on the prevention and control of myopia for primary school students. Methods　 October 2022, Cluster sampling was adopted by our research group to obtain the vision levels of 2278 primary school students employing a diopter test in the Science City Area. In addition, questionnaires were distributed to help us find the risk factors associated with pre-myopia. Results The prevalence rate of pre-myopia among primary school students in the Science  City Area was 45.27%, of which 43.82% were boys and 46.92% were girls, with no statistically significant difference in the prevalence rate of myopia between boys and girls (c2 =2.171, P=0.141). Multiple logistic regression analysis demonstrated that the main risk factors for pre-myopia were having at least one parent with severe myopia, spending less than 2 hours a day outdoors, lack of sleep looking at electronic screens for more than 1 hours, and having an improper reading and writing posture. Outdoor activity time less than 2 hours per day, lack of sleep, looking at the electronic screen for more than 1 hour per day, and incorrect reading and writing posture were all positively associated with the pre-myopia (P values < 0.05). Conclusion The Science City Area has a high prevalence rate of pre-myopia among primary school students. It is proposed that students, schools, families, and local authorities work together to increase the time spent outdoors, get adequate sleep, reduce the time spent staring at digital screens and develop scientific use of eye habits.